CODE SWITCHING IN SOCIAL MEDIA: SELF LEARNING MEDIA OF ENGLISH AS FOREIGN LANGUAGE IN THE ASEAN ECONOMIC COMMUNITY - Cindy Kurnia Octaviyanti (Proceedings Education and Language International Conference, 2017)
English has been an international language for the world, which means English will be used in any occasions when people around the world gather. It becomes a language that should be used in International forum. This situation makes English becomes a language that everyone in the world should conquer. Not all countries in the world use English as their mother language, some countries utilize English as foreign language. Thus, there are many methods so people are able to speak English. One of the methods is by self-learning. The phenomenon happens in the world of todays is people will have a self-learning process throughout social media by using code switching method. People unconsciously used code switching which makes them become bilinguals. This method could help people in learning English. It helps people a lot in mastering English which supposed to be one of a must language skills to face Asean Economic Community era. This paper uses descriptive qualitative approach which identified code switching method in learning English. The data for analysis were collected by library research. By this research, it shows one of methods in learning English so Asians could be well-prepared in taking part of Asean Economic Community. Keywords: code switching, social media, self learning, foreign language, asean economic community